Diagnosis and management of recurrent herpetiform stomatitis and Behçet syndrome like recurrent aphthous stomatitis herpetiform type - Wulandari, Endah Ayu Tri; Subita, Gus Permana (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
Recurrent Aphthous Stomatitis (RAS) is a common inflammatory condition of the oral mucosa. The aetiology of RAS remains unclear, yet there are several predisposing factors which could be involved in the onset of the lesion. The herpetiform type of RAS appeared to be similar to recurrent oral Herpes Simplex infection and also could be part of Behçet Syndrome. This case report discussed a patient suffering from a herpetiform type of RAS with its clinical appearance resembling recurrent oral Herpes Simplex infection and Behçet syndrome. Initial treatment was undertaken based on the empirical treatment, yet the respond was not satisfactory. Then, laboratory tests were undertaken, including complete blood count, the total population of T lymphocyte, B lymphocyte, T helper, T suppressor, NK cells, T helper/T suppressor ratio, C3, C4, IgG, IgA, and IgM. These tests showed that there were immune and hematinic deficiency condition. Nevertheless, the clinical appearance, laboratory findings and consultation did not support the diagnosis of recurrent oral Herpes Simplex infection and Behçet Syndrome, thus, enhancing the definite diagnosis of the herpetiform type of RAS with immune and hematinic deficiency as the underlying condition. Based on the definite diagnosis, treatment plan was then revised to target the underlying condition.